Given f, of, x, equals, minus, x, minus, 3f(x)=−x−3, find f, of, minus, 2f(−2

1 answer

To find f(-2), we substitute x = -2 into the equation:

f(x) = -x - 3

f(-2) = -(-2) - 3

Simplifying this we get:

f(-2) = 2 - 3

f(-2) = -1

So, f(-2) = -1.
Similar Questions
  1. Which equation has the solution x, equals, 3x=3?Answer Multiple Choice Answers 2, x, minus, 7, equals, minus, 12x−7=−1 8, x,
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 5 answers
  2. Write the augmented matrix for the following system of equations.minus, 4, minus, 2, z, equals, minus, y −4−2z= −y minus,
    1. answers icon 1 answer
more similar questions